PERAN ORGANISASI KEMAHASISWAAN INTRAKAMPUS DALAM MENGEMBANGKAN KECERDASAN INTERPERSONAL MAHASISWA - Fitri Oviyanti (El-Idare, 2016)
Student organizations is a means for personal development of students. The aim of this study; a) determine the level of interpersonal intelligence of students active in UKMK KOPMA UIN Raden Fatah Palembang; b) determine the forms of activity in the UKMK KOPMA UIN Raden Fatah Palembang; c) determine the role of activities the UKMK KOPMA UIN Raden Fatah Palembang students in developing interpersonal intelligence. This study used a qualitative approach and methods of ethnography with emic perspective with data analysis includes domain analysis, taxonomic analysis, componential analysis, and analysis of cultural themes. Then come the following conclusion; a) the level of interpersonal intelligence of students active in UKM KOPMA average percentage of 78.61%. b) forms of student activities there UKMK KOPMA classified into three, namely cognitive development activities, capacity building activities affective, and psychomotor development activities. c) each of these activities play an active role in developing the student interpersonal intelligence that includes the dimension of social sensitivity, social understanding and social communication.